Aplikasi Perencanaan Wisata di Malang Raya dengan Algoritma Greedy - Akhmad Eriq Ghozali; Budi Darma Setiawan; Muhammad Tanzil Furqon (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Malang raya is one of regions which becomes the main objective place to visit because it has many tourism places. The thing which has to be noticed is determining the tourism schedule, every tourist must choose the shortest distance and time to be able to reach that destination because they can save the time. To reach that destination, it is used greedy algorithm with knapsack problem to assist the optimation process against searching the shortest traveling time and how many tourism places which can be visited from the possessed time. Time allocation which is possessed by the user to tour is used as an integrity in calculating this application, while the traveling time at each tourism locations which are also used as an integrity is time data which is gotten from google maps. With thats data, the application with greedy algorithm will calculate the most optimal location to be visited with the time which belongs to the user. According to the result of testing application with ten sample of problem cases gets accuracy result 90% from two models of greedy algorithm calculation in searching location which can be visited by the allocation time which is owned. While the result of optimal tour accuracy that is visited is 0% from the first model of calculation and 80% from the second calculation.